Design of Low Subsonic Wind Tunnel with Open Return System for Testing Wind Turbines at Low Airspeeds - Yanel, Karnova; Yanto, Asmara (Universitas Muhammadiyah Jakarta, 2023)
The The Republic of Indonesia is rich in potential for renewable energy, including abundant wind energy. This study aims to design a subsonic open return wind tunnel for testing wind turbines at low airspeeds. The testing focus includes the evaluation of blade efficiency, bearing performance, and other aspects. Testing at low airspeeds (<5 m/s) is highly relevant to the wind conditions in Indonesia. The design process utilizes Computer Aided Design (CAD), while data collection and analysis are conducted through Computer Aided Engineering (CAE) simulations and theoretical calculations. The wind tunnel comprises components such as contraction, honeycomb, test section, diffuser, and support structure. Airflow over the turbine blades can be observed using smoke visualization in the test section. This research is expected to provide practical contributions to the development of low-speed wind turbines in Indonesia.